Leadership Recruitment at the Department of Population and Civil Registration of North Sumatra Province - Ira Juliani; Nina Salmaniah Siregar; Rudi Salam Sinaga (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The aims of this study is to find out Leadership Recruitment at the Department of Population and Civil Registration of North Sumatra Province. This study use qualitative research method. Based on the results that determine the success of the recruitment of the head of the population and civil service, it begins with the stages that have been determined by the selection committee and assessed by the committee of the performance appraisal team, each of which has had the requirements determined by the regulations of the domestic ministry. The requirements that must be met by prospective candidates are in the form of performance competence, education and rank of positions that have met the requirements.determining the success of the recruitment of the head of the population and civil registry office based on the results of the auction of the selection committee team and the performance appraisal team, who is the candidate who passes the interview selection and the explanation of the paper that has been made by each candidate and the highest ranking score will be the winner for the candidate candidate and will be the head of the population and civil registry office.